Tsunami Modeling In The Mentawai Island As A Study Material For Disaster Mitigation (Case Study: Mentawai Earthquake, October 25, 2010) - Khoiridah, Sayyidatul; Prabawa, Septa Erik; ,, Pamudi; Danta, Rama Saputra; Renata, Ahmad Reyhan Cahya; Hamzah, Mochamad Farhan (Jurnal Fisika dan Aplikasinya, 2025)
There was an earthquake in Mentawai on October 25, 2010 which resulted in 509 deaths, 17 people injured, and 11.425 people displaced. Based on this, tsunami modeling was conducted using L-2008 software. This study aims to determine the value of the earthquake source mechanism and conduct tsunami modeling. Tsunami modeling includes earthquake source modeling as a tsunami generator (source modeling), tsunami wave propagation modeling (ocean modeling), and tsunami height modeling (run-up modeling). In this study, bathymetry data and earthquake source mechanism data from the USGS agency were used. The calculation results showed that the Mentawai earthquake had a fault length of 218,78 km, fault width of 45,70 km, and slip of 3,84 m. While the results of tsunami modeling show that the vertical displacemeht value obtained is the maximum value of 1,55 m and the minimum value is -1,55 m. The ocean modeling results show that the tsunami waves reached Sipora Island, North Pagai, and South Pagai at 20 minutes and 50 seconds. While the simulation results of tsunami run up modeling show that the maximum run up is at Sabeugunggu bay with run up value of 6,34 meters. Tsunami run up modeling has an RMSE value of 0,73.